Preparation of hyaluronic acid injectable hydrogel with SHED-derived exosomes and its anti-inflammatory and osteogenic effects on periodontitis: An experimental study in the rat - YING Qiao; YU Yiqiang; SU Jiansheng (Kouqiang hemian waike zazhi)
[Objective:] Preparation of injectable hyaluronic acid (HA) hydrogels loaded with exosomes (EXO) of stem cells from human exfoliated deciduous teeth (SHED) to investigate its anti-inflammatory and osteogenic effects in periodontitis. [Methods:] SHED EXO was extracted and loaded with high molecular weight HA as matrix to synthesize injectable HA hydrogel (SHED-HA) and its degradation rate was determined. The biocompatibility of SHED-HA was analyzed by CCK-8 method, and the osteogenic induction and inflammatory inhibition of SHED-HA were studied by real-time quantitative polymerase chain reaction(RT-qPCR). Subsequently, the effect of SHED-HA on alveolar bone defect in mice was analyzed by micro-CT.  [Results:] SHED-HA had a suitable degradability at the concentration of 6% w/v HA. CCK-8 results showed that SHED-HA had good biocompatibility. RT-qPCR results showed that the expression levels of inflammatory genes IL-1β and IL-6 were down-regulated in the SHED-HA group, while the expression levels of osteogenic differentiation related genes Runx2,OPN and OCN were up-regulated. In vivo experiments showed that SHED-HA reduced alveolar bone destruction in mice. [Conclusion:] The HA hydrogel SHED-HA of SHED exosome was successfully constructed, and it was found that SHED-HA has anti-inflammatory and osteogenic effects on mouse periodontitis.